Complications and Safety of Preconception Low-Dose Aspirin Among Women With Prior Pregnancy Losses. Issue 4 (April 2016) - Ahrens, Katherine A.; Silver, Robert M.; Mumford, Sunni L.; Sjaarda, Lindsey A.; Perkins, Neil J.; Wactawski-Wende, Jean; Galai, Noya; Townsend, Janet M.; Lynch, Anne M.; Lesher, Laurie L.; Faraggi, David; Zarek, Shvetha; et al.
Abstract : OBJECTIVE: To evaluate complications and safety of preconception low-dose aspirin in 1, 228 U.S. women (2007–2011). METHODS: Evaluation of the safety of low-dose aspirin in the participants and their fetuses was a planned secondary analysis of the Effects of Aspirin in Gestation and Reproduction trial, a multicenter, block-randomized, double-blind, placebo-controlled trial investigating the effect of low-dose aspirin on the incidence of live birth. Women aged 18–40 years with a history of one to two pregnancy losses trying to conceive were randomized to daily low-dose aspirin (81 mg, n=615) or placebo (n=613) and were followed for up to six menstrual cycles or through gestation if they became pregnant. Emergency care visits and possible aspirin-related symptoms were assessed at each study follow-up using standardized safety interviews. In addition, complications for both the participant and her fetus or neonate were captured prospectively using case report forms, interviews conducted during pregnancy and postpartum, and medical records. RESULTS: The proportion of women with at least one possible aspirin-related symptom during the trial was similar between treatment arms (456 [74%] low-dose aspirin compared with 447 [73%] placebo, P =.65) as was the proportion with at least one emergency care visit (104 [17%] low-dose aspirin compared with 99 [16%] placebo, P =.76). Maternal complications were evenly distributed by treatment arm with the exception of vaginal bleeding, which was more commonly reported in the low-dose aspirin arm (22% compared with 17%, P =.02). The distribution of fetal and neonatal complications—which included three stillbirths, three neonatal deaths, and 10 neonates with birth defect(s)—was similar between treatment arms. CONCLUSION: Although rare but serious complications resulting from low-dose aspirin cannot be ruled out, preconception low-dose aspirin appears to be well tolerated by women trying to conceive, women who become pregnant, and by their fetuses and neonates. Abstract : Preconception low-dose aspirin appears to be well-tolerated by women trying to conceive, women who become pregnant, and their fetuses and neonates.